(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRAK The purpose of this study was to find out the effect of occupational health and safety on employee performance at PT. Pelni Labuan Bajo. This study used quantitative research type with causal associative quantitative research type, namely for causal relationships between two or more variables from several populations for the sample. With a population of 40 employees. The data were analyzed using a simple linear regression formula. The results showed the testing indicators of occupational health and safety variables on employee performance partially had a positive and significant influence. The results of this study indicated testing the variables of health and work safety on employee performance simultaneously. It showed the t count value of 3,143. This showed that the t count value was greater than the t table value of 1,687 which was obtained from (n -3 = 40-3 = 37 ) with a significant level of a = 0.05. It concluded that tcount > ttable (3.143 > 1.687) So it that the H1 decision was accepted, this meant that the occupational health and safety variable had a positive and significant effect on the employee performance variable. Keywords: Effect, occupational health and safety, employee performance